2012
DOI: 10.5888/pcd9.120082
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Policy Interventions to Reduce Youth Hookah Smoking in the United States

Abstract: Preventing youth smoking initiation is a priority for tobacco control programs, because most adult tobacco smokers become addicted during adolescence. Interventions that restrict the affordability, accessibility, and marketing of cigarettes have been effective in reducing youth cigarette smoking. However, increasing numbers of youth are smoking tobacco using hookahs. Predictors of smoking tobacco with hookahs are the same as those for smoking cigarettes. Established interventions that curb youth cigarette smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 16 publications
(22 reference statements)
3
51
1
1
Order By: Relevance
“…There is little research on product purchasing patterns for cigarettes and alternative tobacco products for young adults. However, price and tax differentials make cigarettes more expensive than other combustibles in the United States [61][62][63][64] and this may influence which groups purchase cigarettes or non-cigarette combustibles at retail outlets Note. GED = graduate equivalency degree; MSA = metropolitan statistical area; SE = standard error.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research on product purchasing patterns for cigarettes and alternative tobacco products for young adults. However, price and tax differentials make cigarettes more expensive than other combustibles in the United States [61][62][63][64] and this may influence which groups purchase cigarettes or non-cigarette combustibles at retail outlets Note. GED = graduate equivalency degree; MSA = metropolitan statistical area; SE = standard error.…”
Section: Discussionmentioning
confidence: 99%
“…However, the research on cigarette warning labels shows that labels are effective in deterring cigarette smoking among college students (23)(24)(25). This research has also shown that the type of cigarette warning labels used (graphic images of disease, images of suffering with testimonials, or emotional tone) affects students differently depending on their smoking status (25).…”
Section: Introductionmentioning
confidence: 98%
“…Raising excise taxes on hookah tobacco products and accessories would deter some students from initiating hookah tobacco smoking. Research on cigarette sales has also shown that taxation is effective in lowering prevalence of consumption (102) and that youth and young adults are two to three times more likely to reduce their tobacco use when prices increase than older adults (23).…”
Section: Limiting Access To Hookah Tobacco Productsmentioning
confidence: 99%
“…The growth in waterpipe use is creating calls for improved control by applying the same regulatory strategies proven successful with cigarettes: increasing the tax on pipe tobacco, applying warning labels to waterpipe tobacco, and banning flavoured tobacco in waterpipes (8,9,12). While the experience of regulating cigarettes will inform the effort to control waterpipe use, important differences may exist between waterpipes and cigarettes that may complicate regulation (13).…”
Section: Introductionmentioning
confidence: 99%